2021
DOI: 10.3390/ma14081888
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Polypropylene, Glass and Steel Fiber on the Thermal Properties of Concrete

Abstract: The variety of approaches to tackle climate change reflects the size of this global problem. No technology will act as a panacea to cure the greenhouse gas emissions problem, but new building materials with byproducts or even wastes have the potential to play a major role in reducing the environmental impacts of the building sector. In this study, three potential solutions of concrete with dispersed reinforcement in the form of recycled fibers (polypropylene, glass and steel) were examined. The aim is to prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 60 publications
5
9
0
Order By: Relevance
“…With the addition of 5%, 10% and 15% of lathe waste, an increase in specific heat by 10.4%, 14.8% and 23.0% respectively was obtained compared to the base sample. The obtained correlation is similar to concrete with steel fibers [14]. Analogously to other mechanical properties, it can be observed that the slope of the obtained curve for correlation between splitting tensile strength and lathe waste content is very similar to relationships determined by other scientists [21,53], especially to the results obtained by Purohit et al [21] (Figure 12).…”
Section: Thermal Propertiessupporting
confidence: 87%
See 2 more Smart Citations
“…With the addition of 5%, 10% and 15% of lathe waste, an increase in specific heat by 10.4%, 14.8% and 23.0% respectively was obtained compared to the base sample. The obtained correlation is similar to concrete with steel fibers [14]. Analogously to other mechanical properties, it can be observed that the slope of the obtained curve for correlation between splitting tensile strength and lathe waste content is very similar to relationships determined by other scientists [21,53], especially to the results obtained by Purohit et al [21] (Figure 12).…”
Section: Thermal Propertiessupporting
confidence: 87%
“…With the addition of 5%, 10% and 15% of lathe waste, an increase in specific heat by 10.4%, 14.8% and 23.0% respectively was obtained compared to the base sample. The obtained correlation is similar to concrete with steel fibers [14].…”
Section: Thermal Propertiessupporting
confidence: 75%
See 1 more Smart Citation
“…In recent years, many studies concerning new generations of concretes have been published, including high-performance concrete (HPC), self-compacting concrete (SCC), eco-efficient concrete, and even self-healing concrete [1][2][3]. One of the most interesting and widely used is fibre-reinforced concretes fibre [4][5][6], including recycled fibre [7][8][9]. The fibre-reinforced concretes are characterised by superior resistance to crack propagation and cracking itself (by fibre bridging on a crack), impact, and fatigue, having good durability at the same time [10].…”
Section: Introductionmentioning
confidence: 99%
“…This state of affairs opens up new opportunities for tuning properties of resulting graphene-based materials by varying their oxidation degree. Having this in mind, we presume that studying aging-related alterations of graphene derivatives can be of great interest for practical purposes, as materials’ properties and performances are some of the most important issues regarding different types of commercially available products [ 30 , 31 , 32 ]. The primary motivation upon which this study relies is to check whether or not storage time alters the morphology and ionic conductivity of graphene oxide flakes.…”
Section: Introductionmentioning
confidence: 99%